Laboratory Study Of Sugarcane Bagasse Carboxymethyl Cellulose (CMC) Puruty on Filtration Loss in Drilling Mud - Idham Khalid (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Drilling mud plays an important role in drilling operations, one of which is controlling filtration loss, which can affect formation stability. One common additive used to reduce filtration loss is Carboxymethyl Cellulose (CMC). This study aims to examine the effect of CMC purity synthesized from bagasse on the filtration loss value in drilling mud. Bagasse as an additive is processed through several chemical stages to produce CMC with a certain level of purity. CMC purity characteristics are carried out to determine purity and then compare performance with commercial CMC with concentrations of 2, 4, 6, and 8 grams. This test was carried out using the standard API filtrate test for 30 minutes. The results showed that increasing the concentration of CMC and commercial CMC reduced the filtrate loss value. CMC from bagasse with a purity of 99.64% showed excellent results and the results for filtration loss testing showed that it could be 14-10.8 ml, mud cake thickness of 1.37-1.54 mm, density of 8.53-8.59 ppg.